ANALISIS HUKUM INTERNASIONAL MENGENAI PELANGGARAN HAK ASASI MANUSIA YANG DILAKUKAN OLEH PASUKAN PENAJAGA PERDAMAIAN PERSERIKATAN BANGSA-BANGSA - I Putu Dwika Ariestu; Ida Bagus Wyasa Putra; Ida Bagus Erwin Ranawijaya (Kertha Negara : Journal Ilmu Hukum, 2013)
This paper aims to analyze the state jurisdiction in the resolution of human rights abuses by UN peacekeepers from the perspective of International law. Comparative study and analysis of the data used to determine the extent of the jurisdiction of the state role in the resolution of cases of human rights violations committed by UN peacekeepers. This study shows that, tasks and functions carried by UN peacekeepers must be in accordance with the provisions of international law including the UN Charter, the International Human Rights Law, International Humanitarian Law, and Security Council mandates. This study also shows that UN peacekeepers committing human rights violations received special immunity as stated on UNSOFA (United Nation Status of Force Agreement) Paragraphs 24, 31, and 47 (b ), but if the case of human rights violations is serious, systematic and widespread impact the jurisdiction of the ICC (International Criminal Court) which applies to the record, that the country is willing to surrender his troops violated the perpetrators to justice in accordance with the jurisdiction of the ICC, it is given that the ICC complement of the court is a domestic court.